2012
DOI: 10.1111/j.1399-0039.2012.01929.x
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐146a polymorphism is associated with asthma but not with systemic lupus erythematosus and juvenile rheumatoid arthritis in Mexican patients

Abstract: Extensive research has shown that aberrant expression of microRNAs (miRNAs) plays an important role in innate and adaptive immune responses. The rs2910164 polymorphism has been identified as a functional variant, which affects the transcription and expression level of miR-146a and, thereby, contributes to the pathogenesis of several inflammatory and autoimmune diseases. To investigate whether the rs2910164 G/C polymorphism was associated with asthma, systemic lupus erythematosus (SLE) or juvenile rheumatoid ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 37 publications
3
36
0
Order By: Relevance
“…Several studies have examined the association between the miR-146a rs2910164 polymorphism and autoimmune diseases, including RA [8], SLE [8,9] and MS [19]. Although previous studies have suggested that many autoimmune diseases share common predisposing factors, the results are inconsistent [26].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Several studies have examined the association between the miR-146a rs2910164 polymorphism and autoimmune diseases, including RA [8], SLE [8,9] and MS [19]. Although previous studies have suggested that many autoimmune diseases share common predisposing factors, the results are inconsistent [26].…”
Section: Discussionmentioning
confidence: 84%
“…In this study, the observation that females have a higher MS prevalence than males may result from an interaction between the genotype and sex hormones during development. Gender-dependent associations have been shown in other case-control studies involving immune entities [8]. As the miR-146a gene is located on 5q33.3, one of the richest loci for genes associated with autoimmune diseases, the linkage disequilibrium between rs2910164 and SNPs near miR-146a (such as rs2431697 and rs2277920) or in other candidate genes ( ADRB2, IL-12, IL-4, IL-13 ) should also be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…76 ). additionally, no association was found in two ethnicities included in the studies, namely caucasian -mexican and european 66,71,77 and asian -chinese Han nationality 66,67 .…”
mentioning
confidence: 75%
“…miR-146 is a negative regulator of signaling pathways in the Th1 response (TLR, TRAF-6 and IRAK1). It targets NFκB regulation by inhibiting IRAK1 and TRAF-6, leading to a reduction of the downstream production of various inflammatory mediators (TNFα and IL-1β) [102,[106][107][108][109][110]. The ERA subtype of JIA features an increased mRNA expression of IRAK4, IRAK1 and TRAF-6 in peripheral blood and synovial fluid mononuclear cells [111].…”
Section: Mirnasmentioning
confidence: 98%